PENDIDIKAN KELUARGA PADA KEBUDAYAAN JAWA: Studi Kasus Keluarga Jawa di Kelurahan Kamal - Aftanjani, Nur Cholis; Safitri, Desy (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
This research purpose to obtain data on the role of the family as the first education of children, then to preserve the Javanese culture as identity, and to raise awareness of the importance of family education in the future development of children, both in attitude and knowledge. The research method used is descriptive with data collection techniques through questionnaires, as well as interviews and literature study. The sample of this research is children of Javanese family who live in West Jakarta area Kamal village. The results of this study concluded that the process of parents in educating children and preserving the local culture has various ways in its implementation, it is done in a sustainable and gives the impression that the effect until the child has entered adulthood, although living in the modern era and there are various influences in it, but the culture can still be run even in small intensity, so that culture is maintained awake from generation to generation.